Teologi, filsafat keilahian, dan spiritualitas: problematika lokus ilmu teologi dalam sistem pendidikan nasional Indonesia - Rachmadi, Simon (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2021)
This article criticizes the way of thinking of the Indonesian Statute of Higher Education known as “Undang-undang No. 12 Tahun 2012”, which puts the academic discipline of theology into the realm of religious science which must be fostered, coordinated, and supervised by the Ministry of Religion. This placement has been brought about injudiciously regardless of the reality on the ground where—for many years in Indonesia—the efforts of doing higher education on theology have been carried out by many Christian communities using their consideration freely: whether to have their theological schools registered by the Ministry of Religion or whether to have them registered by the Ministry of Education. Evaluating the philosophy of the Statute, this article argues about a misconception regarding the idea of “theology” in the Indonesian system of national education. By showing the misconception, this article suggests an alternative direction for public policy: that the academic discipline of theology should be explicitly recognized in Indonesia not only as a science of religious life registered by the Ministry of Religion but also as a science of humanities registered by the Ministry of Education. AbstrakArtikel ini menghadirkan kritik atas cara berpikir UU No. 12 Tahun 2012 yang meletakkan ilmu teologi ke wilayah rumpun ilmu agama yang harus dibina, dikoordinasi, dan diawasi oleh Kementerian Agama. Tampaknya, peletakan ini dilakukan secara sembrono tanpa memerhatikan kenyataan lapangan yang me-nunjukkan bahwa selama bertahun-tahun usaha pengembangan ilmu teologi di Indonesia telah dilakukan oleh masyarakat Kristen dengan pilihan bebas: apa-kah hendak dikembangkan di bawah binaan Kementerian Agama ataukah di ba-wah binaan Kementerian Pendidikan. Dalam artikel ini, kritik digulirkan dengan memperlihatkan adanya miskonsepsi—pada cara berpikir undang-undang ter-sebut—atas ilmu teologi. Dengan memperlihatkan miskonsepsi itu, artikel ini bermaksud menunjuk suatu arah alternatif bagi kebijakan publik: supaya disi-plin ilmu teologi tidak dengan semena-mena diletakkan di wilayah rumpun ilmu agama yang dibina oleh Kementerian Agama namun juga diakui secara eksplisit di Indonesia sebagai wilayah rumpun ilmu humaniora yang dibina oleh Kemen-terian Pendidikan.